Gender Representation in the "Kartini" (2017) Movie by Hanung Bramantyo - Ariesha Meivia Anggraini (International Review of Social and Cultural Studies, 2025)
This study examines gender representation in Hanung Bramantyo's KARTINI (2017), which depicts Raden Ajeng Kartini's struggle for women's rights amidst patriarchal domination. Using a qualitative approach, this analysis highlights Kartini's character as a symbol of emancipation, as well as the important role of education in women's empowerment. The film also explores Kartini's internal conflicts between social demands and personal ambitions, and shows the support of male characters as an important aspect in the fight for equality. The results show that the film not only honors history, but is also relevant to contemporary gender issues, encouraging discussion and reflection on women's rights in today's society.